Ab extra and intra of Tuvan archaization - Ivahnenko, Evgenii N. (The New Research of Tuva, 2013)
Review to: Lamazhaa Ch.K. Society archaization. Tuvan phenomenon. M.: Librocom Publishers, 2013. — 272 p.